Expression of adhesion and extracellular matrix genes in human blastocysts upon attachment in a 2D co-culture system. (26th May 2018) - Aberkane, A; Essahib, W; Spits, C; De Paepe, C; Sermon, K; Adriaenssens, T; Mackens, S; Tournaye, H; Brosens, J J; Van de Velde, H
Abstract: STUDY QUESTION: What are the changes in human embryos, in terms of morphology and gene expression, upon attachment to endometrial epithelial cells? SUMMARY ANSWER: Apposition and adhesion of human blastocysts to endometrial epithelial cells are predominantly initiated at the embryonic pole and these steps are associated with changes in expression of adhesion and extracellular matrix (ECM) genes in the embryo. WHAT IS KNOWN ALREADY: Both human and murine embryos have been co-cultured with Ishikawa cells, although embryonic gene expression associated with attachment has not yet been investigated in an in vitro implantation model. STUDY DESIGN, SIZE, DURATION: Vitrified human blastocysts were warmed and co-cultured for up to 48 h with Ishikawa cells, a model cell line for receptive endometrial epithelium. PARTICIPANTS/MATERIALS, SETTING, METHODS: Six days post-fertilization (6dpf) human embryos were co-cultured with Ishikawa cells for 12, 24 (7dpf) or 48 h (8dpf) and attachment rate and morphological development investigated. Expression of 84 adhesion and ECM genes was analysed by quantitative PCR. Immunofluorescence microscopy was used to assess the expression of three informative genes at the protein level. Data are reported on 145 human embryos. Mann–Whitney U was used for statistical analysis between two groups, with P < 0.05 considered significant. MAIN RESULTS AND THE ROLE OF CHANCE: The majority of embryos attached to Ishikawa cells at the level of the polar trophectoderm; 41% of co-cultured embryos were loosely attached after 12 h and 86% firmly attached after 24 h. Outgrowth of hCG-positive embryonic cells at 8dpf indicated differentiation of trophectoderm into invasive syncytiotrophoblast. Gene expression analysis was performed on loosely attached and unattached embryos co-cultured with Ishikawa cells for 12 h. In contrast to unattached embryos, loosely attached embryos expressed THBS1, TNC, COL12A1, CTNND2, ITGA3, ITGAV and LAMA3 and had significantly higher CD44 and TIMP1 transcript levels ( P = 0.014 and P = 0.029, respectively). LAMA3, THBS1 and TNC expressions were validated at the protein level in firmly attached 7dpf embryos. Thrombospondin 1 (THBS1) resided in the cytoplasm of embryonic cells whereas laminin subunit alpha 3 (LAMA3) and tenascin C (TNC) were expressed on the cell surface of trophectoderm cells. Incubation with a neutralizing TNC antibody did not affect the rate of embryo attachment or hCG secretion. LARGE SCALE DATA: None. LIMITATIONS, REASONS FOR CAUTION: This in vitro study made use of an endometrial adenocarcinoma cell line to mimic receptive luminal epithelium. Also, the number of embryos was limited. Contamination of recovered embryos with Ishikawa cells was unlikely based on their differential gene expression profiles. WIDER IMPLICATIONS OF THE FINDINGS: Taken together, we provide a 'proof of concept' that initiation of the implantation process coincides with the induction of specific embryonic genes. Genome-wide expression profiling of a larger sample set may provide insights into the molecular embryonic pathways underlying successful or failed implantation. STUDY FUNDING AND COMPETING INTEREST(S): A.A. was supported by a grant from the 'Instituut voor Innovatie door Wetenschap en Technologie' (IWT, 121716, Flanders, Belgium). This work was supported by the 'Wetenschappelijk Fonds Willy Gepts' (WFWG G142 and G170, Universitair Ziekenhuis Brussel). The authors declare no conflict of interest.